2006
DOI: 10.1111/j.1471-1842.2006.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Achieving change through mutual development: supported online learning and the evolving roles of health and information professionals

Abstract: Introduction : Major changes in health care, within an information-and technology-rich age, are impacting significantly on health professionals and upon their education and training. Health information professionals-in both the National Health Service (NHS) and higher education (HE) contextsare consequently developing their roles, skills and partnerships to meet the needs of flexible education and training. This article explores one facet of this-supported online learning and its impact on role development. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24][25][26][27] Three additional studies were identified from the references of the included papers 28-30 and 3 were located by citation searching of the included studies. [31][32][33] For full results, see the QUO-ROM flow chart~FIGURE 1!. The total number of studies included in this review therefore was 19~brief details are given in TABLE 1!.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27] Three additional studies were identified from the references of the included papers 28-30 and 3 were located by citation searching of the included studies. [31][32][33] For full results, see the QUO-ROM flow chart~FIGURE 1!. The total number of studies included in this review therefore was 19~brief details are given in TABLE 1!.…”
Section: Resultsmentioning
confidence: 99%
“…This blended approach might be more attractive to adult learners because of their assumed higher levels of motivation and capability for self-directed learning [11]. Specific pharmacy post-graduate level courses [3] and interprofessional online collaborations in learning and practice for healthcare professionals are also evident [12,13]. E-learning systems have become important tools in the process of the continuing education of pharmacists, especially in Europe, USA, Australia and Canada.…”
Section: Introductionmentioning
confidence: 99%
“…, Bury et al. noted that the authors had found that ‘overall, e‐learning was effective, but that it is dependent upon the way it is implemented and the attitude and skills of the learner’ (p. 24) 9 . Thus a library’s support for program implementation, and in the development of their users’ information literacy skills could be seen as critical to the effectiveness of elearning programs.…”
Section: Methodsmentioning
confidence: 99%